(Re)Traduction commentée de quatre poèmes du livre Les villes tentaculaires, d’Émile Verhaeren - Leurquin, Eric Claude (2024)
This dissertation consists of a commented translation of four texts that make up the collection of poems Les villes tentaculaires. The research also analyzes eventual breaks in the textual equivalences between source and target text, style and textual quality of the Brazilian translator, José Jeronymo Rivera (1999). This work was written by Émile Verhaeren, a Belgian, Flemish, French-speaking poet, published in 1895, republished in 1904, reprinted numerous times and translated into a large number of languages. Verhaeren, according to the critics’ consensus, is a visionary capable of describing, in his time, the megalopolises of the 20th century, and foreseeing those of the 21st century, which invade planetary geography with their road, rail and air tentacles. In Brazil, we find echoes of his poetics in Pauliceia Desvairada, by Mário de Andrade. The book has 9nly9y poems, but for this study we selected 9nly four, to better deepen the analyzed elements. These are symbolist poems in free verse. Our analysis highlights transcreation (CAMPOS, 1973 and 1978) and Costa’s (1992) pragmatic perspective. We will make comments based on the works of Antoine Berman (2007), Henri Meschonnic (1999), Roman Jakobson (1973) and Inês Oseki-Dépré (2006). The use of these theorists’ positions allowed us to carry out a critical analysis, restoring in some passages what seems relevant to us. Our aim was to present a new interpretation and recreation in brazilian portuguese of four poems from “tentacular cities”.